Search for the decay B-s(0) -> D*(-/+)pi(+/-) - Aaij, R; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (2013)
A search for the decay Bs0→D*â̂π± is presented using a data sample corresponding to an integrated luminosity of 1.0 fb-1 of pp collisions collected by LHCb. This decay is expected to be mediated by a W-exchange diagram, with little contribution from rescattering processes, and therefore a measurement of the branching fraction will help us to understand the mechanism behind related decays such as Bs0→π+π - and Bs0→DD̄. Systematic uncertainties are minimized by using B0→D*â̂π± as a normalization channel. We find no evidence for a signal, and set an upper limit on the branching fraction of B(Bs0→D*â̂π±)<6.1(7.8)×10 -6 at 90% (95%) confidence level. © 2013 CERN.